International diversification and multinational firms' risk: do locations of investments matter? - Harjito, Agus; Amin Noordin, Bany Ariffin; Matemilola, Bolaji Tunde; Ashari, Mohamad (Faculty of Economics and Management, Universiti Putra Malaysia, 2018)
Revisiting diversification theory, this article examined the impact of investment locations on the relationship between multinational firms' diversification exercise and risk using data on foreign investment activities from 107 listed companies on the Malaysia stock exchange. The study found that diversification exercise is negatively related to risk for firms investing in non-Asian regions. On the contrary, diversification exercise is positively related to risk for firms investing in the Asian region. The results indicated that firms investing in the Asian region do not obtain benefits from diversification because of the increased risk from positively correlated economies within the Asian region. Conversely, non-Asian regions are obtaining benefit from diversification through negatively correlated economies when investing in non-Asian regions.